Caracterização fenotípica e genotípica de â-lactamases e da diversidade clonal de enterobactérias recuperadas de hemoculturas de pacientes hospitalizados - Luciana Nery Silva (2015)
Healthcare Associated Infections represent a growing challenge due to the increase of antimicrobial resistance. These infections provoke severe harm to the patients health, raise the mortality rates and the medical costs. The main mechanism of antimicrobial resistance in the family Enterobacteriaceae is the production of extended-spectrum -lactamases (ESBL) and carbapenemases. The ESBL-producing enterobacteria show a great ability to disseminate and remain inside the hospital environment, limiting the therapeutic options. Despite the high prevalence of these enzymes, their production is still underestimated because of the difficulties of laboratory detection. The present research aimed to characterize the presence of the main types of ESBL, AmpC and carbapenemases (KPC and NDM) through phenotypic and genotypic methods, and to assess the genetic diversity of 88 enterobacteria recovered from hemoculture in hospitals in Belo Horizonte, MG, between June 2008 and June 2009 and also april 2013 and april 2014. It was carried out antimicrobial susceptibility testing and phenotypic detection of ESBL enzymes through Double-Disk Synergy Test (DDST) and Etest; AmpC, through the Double-Disk Synergy Test and combined disk of cefoxitin with phenylboronic acid and research of carbapenemases, through the Modified Hodge Test (MHT). The genes blaTEM, blaSHV, blaCTX-M, blaGES, blaAmpC, blaCMY, blaFOX, blaDHA, blaKPC and blaNDM were evaluated by the Polymerase Chain Reaction (PCR). In the evaluation of the genetic similarity of the samples, it was used the ERIC-PCR. Among the identified samples, 58% of K. pneumoniae, 21% of Enterobacter cloacae complex, 10% of Enterobacter aerogenes and 11% of E. coli, the frequency of production of ESBL when DDST and Etest were used was of 56.8% and 55.6%, respectively. The phenotypic research of AmpC showed positive only to one sample. Through MHT, 39.2% of the samples of K. pneumoniae and 11.1% of the Enterobacter spp. were positive. Genes which encodes the synthesis of ESBL were observed in 79.5% of the samples. Among them, blaTEM was dominant, detected in 61.3% (54/88) of the samples, followed by blaSHV present in 42% of the samples, especially in K. pneumoniae (36/51). The simultaneous presence of markers which encode two types of ESBL were observed in 37.5% (33/88) of the samples. The combination blaTEM/blaSHV was the most common in K. pneumoniae and blaTEM/blaCTX-M in Enterobacter spp. and E. coli. Regarding the carbapenemases, blaKPC was detected in 45% (23/51) of the samples of K. pneumonia and in 18.5% (5/27) of the samples of Enterobacter spp.. It was detected the presence of blaAmpC in a sample of E. coli which also showed resistance to cefoxitin. The genes blaCMY, blaFOX, blaDHA, blaNDM and blaGES were not detected in any of the bacterial samples analyzed here. The obtained results may suggest that several clonal populations might be circulating among the Hospitals studied, some identical, which can be disseminated through different ways, with health professionals and the patients transferences between hospitals.